COVID-19: Gastrointestinal Manifestations and Complications - Angel Yun-Kuan Thye; Priyia Pusparajah; Loh Teng-Hern Tan; Jodi Woan-Fei Law; Vengadesh Letchumanan; Learn-Han Lee (Progress in Microbes and Molecular Biology)
The virus responsible for the COVID-19 pandemic is the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which belongs to the genus Betacoronavirus. This genus also includes the severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV). The common symptoms of COVID-19 infection are fever and respiratory symptoms, but it can also involve the gastrointestinal tract (GIT), resulting in manifestations such as diarrhea, nausea and/or vomiting and abdominal pain. The emergence of COVID-19 led to public health emphasis on droplet transmission and precautions of contact with respiratory secretions. However, mounting evidence demonstrates detection of SARS-CoV-2 RNA in stool samples of COVID-19 patients. It has also been demonstrated that the host receptor angiotensin-converting-enzyme-2 (ACE-2) is highly expressed not just in respiratory cells but also in gastrointestinal sites involving the glandular cells of gastric, duodenal, and rectal epithelium. This suggests that SARS-CoV-2 can infect the digestive system, serving as another route of transmission. This review aims to study the prevalence of some of the gastrointestinal manifestations following COVID-19 infection and findings of positive SARS-CoV-2 RNA in stool specimens while making parallels to the severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS) infection. We will also discuss the possible pathophysiology of COVID-19 related gastrointestinal involvement.